Nitrification stability and membrane performance under different water permeation intensity of an osmotic membrane bioreactor. (May 2020) - Jeong, Dawoon; Lee, Chang-Ha; Lee, Seockheon; Bae, Hyokwan
Abstract: The effects of water permeation intensity on nitrifying bacterial activity, forward osmosis (FO) membrane performance, and bacterial community structure were investigated in an osmotic membrane bioreactor (OMBR). Ammonia was partially oxidized by controlling acidification buffer concentration. Then, the FO module was externally integrated with a nitrifying bioreactor to examine nitrifying bacterial activity in response to the increased salinity. The salinity gradually increased from 2.7 to 45.7 g.L −1 total dissolved solids (TDS). Inhibition of nitrite-oxidizing activity was initiated at a salt concentration of 36.2 g.L −1 TDS. Complete ammonia-oxidizing bacteria inhibition occurred at 45.7 g.L −1 TDS. Illumina high-throughput sequencing revealed that the bacterial community responded to the operational conditions such as the ammonia loading rate and salt concentration. Only two species, Nitrosomonas eutropha and Nitrobacter winogradskyi, were responsible for nitrification in the OMBR. The cellulose triacetate FO membrane showed poor rejection efficiencies for ammonia, nitrite, and nitrate. The FO module was capable to maximally recover 107.8% water in the OMBR. However, the water permeation intensity should be appropriately adjusted to avoid nitrification failure by maintaining the optimal salinity as lower than 35 g.L −1 TDS, which is equivalent to water permeation efficiency of 107.8% in this study. Graphical abstract: Image 1 Highlights: Increase in water permeation intensity affected nitrifying bacterial activity. Immobilized cells were effective to mitigate membrane fouling in an OMBR. Bacterial community structure responded to ammonia loading rate and salinity. NOB inhibition can be selectively achieved by controlling the salinity. Nitrosomonas eutropha and Nitrobacter winogradskyi were responsible for nitrification.